Use of random amplified polymorphic DNA (RAPD) for identification of Gaeumannomyces species - Fouly H M; Domier L L; Wilkinson H T (Soil Biology and Biochemistry, 1996)
Randomly amplified polymorphic DNAs (RAPD) were used to distinguish among isolates of Gaeoumannomyces graminis var. tritici, G. g. var. graminis, G. g. var. avenae, G. incrustans, and G. cylindrosporous. Of 60 random sequence decamer primers tested, 28 produced bands and 15 showed evidence of polymorphism. Four primers produced DNA amplification patterns that were used to distinguish G. graminis, G. incrustans, and G. cylindrosporous. Banding patterns were similar within isolates of G. g. var. tritici, G. g. var. avenae and G. incrustans. G. g. var. graminis showed greater variability in banding patterns. The unweighted pair group method which arithmetical averages (UPGMA) indicated that G. g. tritici isolates were more closely related to G. g. var. avenae than to G. g. var. graminis isolates. The results of our study showed that RAPD markers can be used to confirm the identification of Gaeumannomyces species and varieties.
Keywords: RAPD